The Early Permian Bolosaurid Eudibamus cursoris: Earliest Reptile to Combine Parasagittal Stride and Digitigrade Posture During Quadrupedal and Bipedal Locomotion - Berman, David S; Sumida, Stuart S.; Henrici, Amy C.; Scott, Diane; Reisz, Robert R.; Martens, Thomas (Frontiers in Ecology and Evolution, 2021)
A comprehensive skeletal description is presented here for the first time of the lower Permian (Artinskian) reptile Eudibamus cursoris from the Bromacker locality of Germany since the brief description of the holotype in 2000 as the only known bolosaurid represented by an essentially complete, well-preserved articulated skeleton. Included in the description here is a superbly preserved, partial, articulated second specimen of E. cursoris discovered at the same locality that includes a short portion of the vertebral column associated with the pelvis and right hindlimb. Descriptions of the holotype and new specimen add substantially to features of the skull and postcranium that not only confirm a bolosaurid assignment, but also add significantly to an already long list of structural features supporting an ability unique among Paleozoic vertebrates to reach relatively high bipedal and quadrupedal running speeds employing a parasagittal stride and digitigrade stance with the limbs held in a near vertical posture. Structural differences between the two specimens are restricted to the tarsi and are attributed to different ontogenetic stages, with the holotype representing a more juvenile individual, and the larger second specimen representing a more mature animal.